Борнове наближення для поляризаційних спостережуваних при розсіянні протонів ядрами 40Ca - Babak, O. V.; Berezhnoy, Yu. A.; Mikhailyuk, V. P. (Publishing house "Academperiodika", 2020)
A development of the optical model for the description of the hadron-nucleus scattering is proposed. When describing the behavior of polarization observables for the elastic proton scattering on 40Ca nuclei in the energy interval from 200 to 800 MeV, the Born approximation is used. Analytical expressions for the scattering amplitudes, as well as for the differential cross-sections and polarization observables, are obtained. The comparison of the scattering observables calculated in the 1st and 2nd Born approximations is made. It is shown that the observables calculated in this approach are in a reasonable agreement with the available experimental data.